Hierarchical cementitious composites developed by sisal fibers and micro crystalline cellulose (MCC) as reinforcements - Filho, Aloysio (2019)
The present research investigated the influence of multi-scale reinforcements [sisal fibers (Agave Sisalana) and microcrystalline cellulose (MCC)] on the mechanical properties of cementitious composites. Aqueous dispersions of MCC were prepared by using two different surfactants namely